2019
DOI: 10.1002/mds.27812
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism and spastic paraplegia type 7: Expanding the spectrum of mitochondrial Parkinsonism

Abstract: Background Pathogenic variants in the spastic paraplegia type 7 gene cause a complicated hereditary spastic paraplegia phenotype associated with classical features of mitochondrial diseases, including ataxia, progressive external ophthalmoplegia, and deletions of mitochondrial DNA. Objectives To better characterize spastic paraplegia type 7 disease with a clinical, genetic, and functional analysis of a Spanish cohort of spastic paraplegia type 7 patients. Methods Genetic analysis was performed in patients susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 47 publications
1
55
0
1
Order By: Relevance
“…Replication in exome data from 1148 European PD patients revealed significant association of heterozygous of p.A510V in SPG7 with PD risk [106]. Another independent study reported that parkinsonism is frequently observed in spastic paraplegia patients with pathogenic variants in SPG7 [25]. These examples demonstrated that despite the limitations of small discovery cohorts, valuable data can Immunoblotting was performed with primary antibodies against ATP10B, the CDC50A Flag-tag and GAPDH, which was used as a loading control.…”
Section: Discussionmentioning
confidence: 99%
“…Replication in exome data from 1148 European PD patients revealed significant association of heterozygous of p.A510V in SPG7 with PD risk [106]. Another independent study reported that parkinsonism is frequently observed in spastic paraplegia patients with pathogenic variants in SPG7 [25]. These examples demonstrated that despite the limitations of small discovery cohorts, valuable data can Immunoblotting was performed with primary antibodies against ATP10B, the CDC50A Flag-tag and GAPDH, which was used as a loading control.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, among 35 SPG7 patients, parkinsonism was observed in 21% of cases. mtDNA copy number quantification in blood revealed significantly lower mtDNA levels in either patients or carriers than controls [78] .…”
Section: Parkinsonismmentioning
confidence: 87%
“…Notably, previous studies have also yielded interesting candidates even with small sample sizes: Guo et al have nominated interesting variants in NUS1 from 39 trios with healthy parents and earlyonset patients with PD (14), and a smaller study of exome sequencing in 50 early-onset patients with PD has nominated interesting variants in SPG7 (11). The SPG7 implication in PD has been independently identified (15). Taken together, although there are limitations, smaller discovery cohorts can still be valuable, and further replication in larger cohorts are warranted.…”
Section: Discussionmentioning
confidence: 99%